2016
DOI: 10.18388/abp.2016_1284
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial progenitor cells participation in cardiovascular and kidney diseases: a systematic review

Abstract: Endothelial progenitor cells (EPCs) represent a small population of blood cells (5-40 cells/mm(3)), with an ability to differentiate into endothelial cells that form the lining of the blood vessels and contribute to postnatal angiogenesis. Abundant evidence shows that recruitment of EPCs from the bone marrow, the monocyte/macrophage lineage and the organs facilitate the endothelial regeneration and repair. Changes in the number of EPCs were observed in both, chronic kidney and cardiovascular diseases. Thus, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 72 publications
0
21
0
Order By: Relevance
“…Moreover, the SDF-1/CXCR4 axis acts as a key regulator of angiogenesis and contributes to the regulation of endothelial progenitor cell (EPC) recruitment in ischemic tissues. EPCs represent a small population of blood cells that can differentiate into endothelial cells and participate in postnatal angiogenesis [47]. In addition, EPCs are involved in physiological and pathological angiogenesis/vasculogenesis [48].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the SDF-1/CXCR4 axis acts as a key regulator of angiogenesis and contributes to the regulation of endothelial progenitor cell (EPC) recruitment in ischemic tissues. EPCs represent a small population of blood cells that can differentiate into endothelial cells and participate in postnatal angiogenesis [47]. In addition, EPCs are involved in physiological and pathological angiogenesis/vasculogenesis [48].…”
Section: Discussionmentioning
confidence: 99%
“…When the endothelium is damaged, the connection between EPCs and stromal cells is weakened due to the influence of some inflammatory cytokines and mobilization factors, such as tumor necrosis factor-a, interleukin-6, and vascular endothelial growth factor, stimulating EPCs mobilization and release from bone marrow to peripheral circulation (Patel et al, 2016). After EPCs enter the peripheral blood, they migrate and adhere to the damaged blood vessels, proliferate and differentiate into mature endothelial cells, promote reendothelialization and neovascularization, so as to maintain the integrity of endothelial structure and repair ischemic tissue (Minhajat et al, 2015;Kiewisz et al, 2016). However, it has been shown that Ang II impairs the proliferative and migratory ability of EPCs, resulting in diminished vascular regeneration (Endtmann et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial progenitor cells (EPCs) are the precursor cells of endothelial cells, which mainly exist in bone marrow, cord blood, and peripheral blood (Murohara et al, 2000). EPCs are quite capable of repairing damaged vascular endothelium and regenerating blood vessel (Altabas et al, 2016;Kiewisz et al, 2016). Therefore, EPCs have a broad prospect in the research and treatment of cardiovascular and cerebrovascular diseases, diabetes, peripheral vascular diseases, and other vascular injury diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial progenitor cells (EPCs) are also involved in the physiological and pathological progression of new vessel formation (Kiewisz, Kaczmarek, Pawlowska, Kmiec, & Stompor, 2016;Patel, Donovan, & Khosrotehrani, 2016). EPCs contain cell surface markers CD133, CD34 and vascular endothelial growth factor receptor-2 (VEGFR2), which facilitate postnatal vasculogenesis (Asahara et al, 1999) and exert regenerative effects.…”
Section: Introductionmentioning
confidence: 99%